La Realidad Aumentada: una herramienta para la elaboración de los papeles de trabajo en una Auditoría (2020)
Augmented reality (AR), is a technology that performs a combination between the real and the digital world, using an electronic device with a camera and specialized software. The use of RA has no limits; being implemented in different areas of knowledge, where they add digital information to a marker; The most commonly used is the QR code. Systems auditing cannot be the exception and you can use it as a tool for executing an audit plan, helping the audit group to unify the preparation of work papers and the presentation of information; vital part for the delivery of the evidence found in the audit report.